Redox-Responsive Lipidic Prodrug Nano-Delivery System Improves Antitumor Effect of Curcumin Derivative C210 - Xin Guo; Min Wu; Yanping Deng; Yan Liu; Yanpeng Liu; Jianhua Xu (MDPI AG, 2023)
The poor bioavailability of curcumin and its derivatives limits their antitumor efficacy and clinical translation. Although curcumin derivative C210 has more potent antitumor activity than curcumin, it has a similar deficiency to curcumin. In order to improve its bioavailability and accordingly enhance its antitumor activity in vivo, we developed a redox-responsive lipidic prodrug nano-delivery system of C210. Briefly, we synthesized three conjugates of C210 and oleyl alcohol (OA) via different linkages containing single sulfur/disulfide/carbon bonds and prepared their nanoparticles using a nanoprecipitation method. The prodrugs required only a very small amount of DSPE-PEG2000 as a stabilizer to self-assemble in aqueous solution to form nanoparticles (NPs) with a high drug loading capacity (~50%). Among them, the prodrug (single sulfur bond) nanoparticles (C210-S-OA NPs) were the most sensitive to the intracellular redox level of cancer cells; therefore, they could rapidly release C210 in cancer cells and thus had the strongest cytotoxicity to cancer cells. Furthermore, C210-S-OA NPs exerted a dramatic improvement in its pharmacokinetic behavior; that is, the area under the curve (AUC), mean retention time and accumulation in tumor tissue were 10, 7 and 3 folds that of free C210, respectively. Thus, C210-S-OA NPs exhibited the strongest antitumor activity in vivo than C210 or other prodrug NPs in mouse models of breast cancer and liver cancer. The results demonstrated that the novel prodrug self-assembled redox-responsive nano-delivery platform was able to improve the bioavailability and antitumor activity of curcumin derivative C210, which provides a basis for further clinical applications of curcumin and its derivatives.